2018
DOI: 10.1016/j.dhjo.2018.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Ethical issues and dentists' practices with children with intellectual disability: A qualitative inquiry into a local French health network

Abstract: There is a wide range of practices but no consensus. This study shed some light on the different perspectives of dentists, most of whom adopted a utilitarianist viewpoint. In this context, ethical reflection is necessary to avoid a detached attitude or, worse, abuse. Further study would enrich this reflection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
0
10
0
1
Order By: Relevance
“…We point out as a limitation of the work that we did not make the determination of salivary flow, due to the difficulty in collection, since patients with CM are more anxious (Camoin, Dany, Tardieu, Ruquet, & Le Coz, 2018;Davila, 1990) and we prioritize their comfort. To minimize salivary flow rate absence, all salivary parameters were expressed in protein concentration.…”
Section: Discussionmentioning
confidence: 99%
“…We point out as a limitation of the work that we did not make the determination of salivary flow, due to the difficulty in collection, since patients with CM are more anxious (Camoin, Dany, Tardieu, Ruquet, & Le Coz, 2018;Davila, 1990) and we prioritize their comfort. To minimize salivary flow rate absence, all salivary parameters were expressed in protein concentration.…”
Section: Discussionmentioning
confidence: 99%
“…According to Camoin et al [15] (2018), practitioners reported sacrificing ethical values, such as patient autonomy, beneficence, and non-maleficence, when making a clinical decision. Most of the dentists adopt a “utilitarianist” viewpoint.…”
Section: Discussionmentioning
confidence: 99%
“…The current field has not been debated broadly as it has quite different concerns and priorities. [15]…”
Section: Introductionmentioning
confidence: 99%
“…Lack of experience has been found by Kadivar et al (2017) to negatively affect how paediatric residents address ethical dilemmas regarding information. A majority of dentists in a study conducted by Camoin et al (2018) claimed that they sometimes sacrificed ethical values (such as patient autonomy) in order to provide beneficial care to anxious children with intellectual disabilities and to address decision-making related challenges; while Australian pharmacists (Hattingh & King, 2019) claim that they generally avoid situations they perceive as requiring complex management. Many Japanese physicians believe that few problems result when they honestly tell cancer patients about their poor prognosis (Elwyn et al, 2002).…”
Section: Strategiesmentioning
confidence: 99%